Ductility and Ultimate Capacity of Prestressed Steel Reinforced Concrete Beams. (28th March 2017) - Wang, Chengquan; Shen, Yonggang; Yang, Runfang; Wen, Zuolin
Abstract : Nonlinear numerical analysis of the structural behaviour of prestressed steel reinforced concrete (PSRC) beams was carried out by using finite element analysis software ABAQUS. By comparing the load-deformation curves, the rationality and reliability of the finite element model have been confirmed; moreover, the changes of the beam stiffness and stress in the forcing process and the ultimate bearing capacity of the beam were analyzed. Based on the model, the effect of prestressed force, and H-steel to the stiffness, the ultimate bearing capacity and ductility of beam were also analyzed.